Efficiency analysis of telecommunications companies in Southeast Asia using Stochastic Frontier Analysis (SFA) method - Riko Hendrawan; Gayuh T Permana; Kristian WA Nugroho (Jurnal Siasat Bisnis, 2019)
This study aims to analyze the efficiency of telecommunications companies and find out the variables of efficiency of telecommunications companies in Southeast Asia in the period of 2008-2017 involving 14 telecommunications operators using the Stochastic Frontier Analysis method. The results of these studies show that the telecommunications companies in Southeast Asia still had room to improve their profit efficiency scores for 0,984 – 0,689 = 0.295. Furthermore, the results show that input variables such as Personal, capex and opex have a positive effect on the value of efficiency which means that each increase in the variable Capex, Opex and Personal Expenses will have an impact in increasing the value of efficiency Whereas the total assets have negative effects on the efficiency value of telecommunications operators. Output variables consisting of revenue, subscribers and ARPU have a significant effect on the value of efficiency. These three output variables in the SFA measurement method have a positive influence on the efficiency of telecommunication operators. Inflation used as an environmental variable in measuring the efficiency of telecommunication operators shows that it does not have a significant impact on the efficiency value of telecommunications operators.This study aims to analyze the efficiency of telecommunications companies and find out the variables of efficiency of telecommunications companies in Southeast Asia in the period of 2008-2017 involving 14 telecommunications operatorsusing the Stochastic Frontier Analysis method. The results of these studies show that the telecommunications companies in Southeast Asia still had room to improve their profit efficiency scores for 0,984 – 0,689 = 0.295. Furthermore, the results show that input variables such as Personal, capex and opex have a positive effect on the value of efficiency which means that each increase in the variable Capex, Opex and Personal Expenses will have an impact in increasing the value of efficiency Whereas the total assets have negative effects on the efficiency value of telecommunications operators.Output variables consisting of revenue, subscribers and ARPU have a significant effect on the value of efficiency. These three output variables in the SFA measurement method have a positive influence on the efficiency of telecommunication operators. Inflation used as an environmental variable in measuring the efficiency of telecommunication operators shows that it does not have a significant impact on the efficiency value of telecommunications operators.